Efficacy of the combination of venetoclax and hypomethylating agents in the treatment of patients with primary, relapsed and/or refractory acute myeloid leukemia - E. V. Usikova; K. D. Kaplanov; V. I. Vorob'ev; T. I. Lobanova; M. A. Ul'yanova; D. G. Kisilichina; Yu. N. Kobzev; D. I. Shikhbabaeva; O. Yu. Vinogradova; V. V. Ptushkin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance and goals. Treatment of patients with acute myeloid leukemia has traditionally been highly intensive and includes induction therapy using cytarabine and anathracyclines. In addition to new opportunities in the treatment of acute myeloid leukemia, the problem of toxicity of high-intensity therapy in elderly and young somatically burdened patients is quite acute. International clinical trials of phases I-III demonstrated a combination of high efficacy and acceptable hematological toxicity of combinations of hypomethylating agents and venetoclax in the first line of therapy, as well as in the treatment of resistant forms and relapses of acute myeloid leukemia in the older age group, which contributed to the study of the effectiveness of combinations of hypomethylating agents and venetoclax in the treatment of similar groups of young comorbid patients. In this work, we evaluated the efficiency of a combination of hypomethylating agents and venetoclax and overall and disease-free survival in patients with acute myeloid leukemia in routine practice.Methods. In the period from October 2017 to December 2021 on the basis of the Department of Hematology No. 11 and the Department of Bone Marrow and Hematopoietic Stem Cell Transplantation No. 56 of the Botkin Hospital (Moscow, Russia) 33 patients with acute myeloid leukemia received venetoclax therapy in combination with decitabine or azacitidine: 14 (42%) men and 19 (58%) women, median age was 60 years (23–83 years). In 42% (14 of 33) of cases, the regimen was prescribed for resistant course or relapse of acute myeloid leukemia and in 61% (20 of 33) as induction therapy. Three patients (15%) out of 19 from the group of newly diagnosed acute myeloid leukemia received this treatment regimen in the first line, taking into account the ECOG status 3-4. By August 2022, 13 (39%) patients are alive, 20 (61%) people have died. Overall survival, the rate of complete remission and complete remission with incomplete recovery, the rate of achieving negativity of minimal residual disease, the frequency of hematological toxicity and infectious complications were assessed. Statistical data processing used: frequency analysis using contingency tables (Fisher's exact test), survival analysis using the Kaplan-Meier method.Results. Complete remission and complete remission with incomplete recovery were achieved in 72.72% (24 of 33) of patients. In the group of primary acute myeloid leukemia, remissions were observed in 80% (16 out of 20) of cases, in the group with resistant course or recurrence of acute myeloid leukemia in 67% (8 out of 12) (p = 0.3). Determination of minimal residual disease by flow cytometry after the 1st course was performed for 54.54% (18 of 33) patients, while negativity was stated in 84.2% (14 of 18 patients) cases. In both groups, the incidence of hematological toxicity and infectious complications are comparable to those according to the literature data. The median follow-up was 9.5 months (1–47). Median overall survival was 39 months, 2-year overall survival was 63%, and overall 4-year survival was 39%. The disease-free survival rate was 33%.Conclusion. The combination of hypomethylating agents and venetoclax showed good efficacy and fairly high overall survival in patients of all age groups, both for primary acute myeloid leukemia and for relapses and resistant forms, regardless of previous therapy. Given the moderate hematological toxicity, as well as the relatively low rates of infectious complications during therapy, including the rather low mortality rates in case of COVID-19 infection in comparison with those on the background of high-intensity courses of therapy for acute myeloid leukemia, this scheme can be widely used not only in patients of the older age group, but also in young comorbid patients.